Semen collection and baseline semen characteristics of the king quail (Synoicus chinesis) - Isabella Wong; Robert Doneley; Stephen Johnston (Theriogenology Wild)
Assisted breeding technology has important management implications for avian conservation and aviculture but species-specific reproductive information is lacking. This study aimed to develop a successful semen collection for the king quail (Synoicus chinesis) in order to establish baseline seminal characteristics and to explore the effect of flock density on seminal quality. A total of 19 quail consisting of 2 groups of 5 and 4 and 1 group of 10 were housed in 3 separate aviaries located at the University of Queensland, Gatton, Australia during Spring. Morphometrics and morphology (normal and abnormal) of the sperm cells were also described by phase contrast and differential interference microscopy. Semen was sucessfully collected by cloacal massage from 90 % of attempts with only minor evidence of faecal or urate contamination. No significant differences in seminal characteristics were found with respect to bird housing density. Mean ± SEM seminal characteristics for 103 ejaculates included volume (1.6 ± 0.02 μL), sperm concentration (8.1 ± 0.5 × 109 mL–1), progressive sperm motility (50.0 ± 0.04 %), rate of sperm motility, (2.9 ± 0.13), pH (6.7 ± 0.2), the percentage of live sperm (88.0 ± 0.01 %) and the percentage of total abnormal sperm morphology (21.0 ± 0.03 %). Cloacal massage proved to be a highly successful technique to collect king quail semen and the seminal characteristics reported here are the future basis of assessing fertility and the application of assisted breeding in the species.